Knowledge, attitudes, beliefs and practices of schoolgoing adolescents living in Gauteng in relation to common cancers and cancer risks - IJsselmuiden, Carel, 1954- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2006.